Praktik Personal Branding Notaris terhadap Batasan, Etika dan Legalitasnya ditinjau dari Undang-Undang Jabatan Notaris dan Kode Etik Notaris: Notary Personal Branding Practices in Relation to Their Limitations, Ethics, and Legality as Reviewed from the Notary Position Law and Notary Code of Ethics - Kurniawan, Arie; Hartanto, Farrel Billie Akmal Fahar Ary; Dewantary, Ariska (Faculty of Law Hang Tuah University, 2025)
Personal branding, understood as the reputation or